Higher Agricultural Education: An Exploratory Study on Skill Gap of Students - , Ananda K. R.; Satyapriya, Sitaram Bishnoi, Preeti Y. H., Ankit Pal, Kotha Shravani (Archives of Current Research International, 2024)
The skill gap among higher education students has become a pressing concern in today's competitive job market, prompting the need for thorough assessment and targeted interventions. This study endeavours to quantify the extent of skill discrepancies among students in higher agricultural education. Through skill gap analysis, the aim is to gauge the shortfall in agricultural and professional competencies among young scholars, delineating the areas where skills are lacking or underdeveloped. By employing an exploratory research design, the study seeks to identify and address skill gaps effectively. The target respondents comprise students from IARI, University of Agricultural Sciences (Raichur), and Banda University of Agriculture and Technology, with a sample size of 150 selected to represent the population adequately. To construct the skill gap index, various dimensions including technical, personal, problem-solving, leadership, entrepreneurial, computer, and organizational skills were pretested. Data collection involved the utilization of questionnaires and in-person interviews to evaluate competency differences among students across the three agricultural universities. Statistical methods such as the Friedman test and the Wilcoxon signed rank test was employed to analyse the gathered data. The analysis found significant disparities in the overall skill levels of students. These findings underscore the need for targeted interventions to bridge the identified skill gaps effectively. By illuminating areas of deficiency, this study provides valuable insights for enhancing the quality of agricultural education and fostering the development of well-rounded professionals equipped to tackle the challenges of the agricultural sector.